Performances of Community Schools towards Students’ Learning and Satisfaction: A Case of Makawanpur and Udayapur Districts - Nepal, Bijaya (International Research Journal of MMC, 2020)
This study was undertaken to analyses the performances of community schools towards students' learning and satisfaction in Makawanpur and Udayapur Districts of Nepal. School performances evaluation, observation tools were used to measure the input, process and output condition of selected schools for the research. This study was conducted from February 2019 to March 2020. The sample size was taken by using cluster sampling method. There were 203 numbers of senior secondary schools in the study area; among them (13.6%) senior 28 secondary schools were taken from both districts. Analysis of the data was done by using SPSS version 20 and the Multi-regression and correlation test was applied to analyze the data.